Analisis Kewajiban Pajak Penghasilan (PPH) Badan Pada PT Setyanata Bersaudara Tahun 2018 - Fina Mariana, Punamawati Helen Wijaya (Jurnal Paradigma Akuntansi, 2021)
Tax collection is one of the most important things in Indonesia, where mostly come from income tax. This research aims to find out the corporate income tax liability at PT Setyanata Bersaudara in 2018, and its accordance with Act. Taxation Number 36 Year 2008. The research method used is descriptive analysis method. The calculation of tax obligations in this research is divided into several articles of income tax and fiscal corrections are made on the company's income statement. The result of this study indicate that PT Setyanata Bersaudara had calculated, payment, and reported corporate income tax in accordance with Act. Taxation Number 36 Year 2008.